2019
DOI: 10.1634/theoncologist.2019-0739
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Response of Cryoablation Followed by Pembrolizumab in a Patient with Metastatic Cervical Carcinosarcoma with High Tumor Mutational Burden: A Case Report

Abstract: Cervical carcinosarcoma is an extremely rare type of neoplasm that lacks standard of care. Preclinical and clinical evidence has suggested that cryoablation in combination with immunotherapy may result in a synergistic effect, generating a more robust immune response to distant lesions. A few clinical trials have evaluated the efficacy of such combination treatment in a variety of solid tumors, but with conflicting results. This report describes the first clinical efficacy of cryoablation followed by pembroliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In addition, mutation of the tumor suppressor gene PTEN is considered to be an early event in the pathogenesis of EC. In the analysis of pathogenic PTEN mutations in EC, researchers found that PTEN mutations were more prevalent in POLE -mutated tumors than in POLE -wild-type tumors with pMMR or dMMR [ 33 ]. In addition, because dMMR may occur later than other mutation processes, it can be wrongly identified as MSS at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mutation of the tumor suppressor gene PTEN is considered to be an early event in the pathogenesis of EC. In the analysis of pathogenic PTEN mutations in EC, researchers found that PTEN mutations were more prevalent in POLE -mutated tumors than in POLE -wild-type tumors with pMMR or dMMR [ 33 ]. In addition, because dMMR may occur later than other mutation processes, it can be wrongly identified as MSS at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 1-3% of colorectal cancers and approximately 7% of endometrial cancers harbored POLE mutation (12,17). Preliminary clinical studies have also revealed the association between POLE/ POLD1 proofreading mutations and beneficial clinical outcomes to ICI therapy in endometrial cancer (18), nonsmall cell lung cancer (19), colorectal cancer (20), and cervical carcinosarcoma (21). A recent study investigated the prevalence of POLE/POLD1 mutations across multiple cancer types in of 47,721 patients from cBioPortal database and demonstrated a potential predictive value of POLE/POLD1 mutations for positive outcomes to ICI treatment (22).…”
Section: Introductionmentioning
confidence: 99%
“…No lesions were detected on CT images at 1.5 months post administration of pembrolizumab, and it was remained for 7 months after the treatment. In another study, a patient with high tumor mutational burden metastatic cervical carcinoma saw an exceptional response to cryoablation followed by pembrolizumab 88 . Cryoablation was also effective in achieving complete response for at least 9 months in another patient who had developed resistance to anti-PD-L1 and anti-CTLA-4 antibody immunotherapy 120 .…”
Section: Combination Cryoablation Cancer Therapiesmentioning
confidence: 98%
“…Recent studies have explored ICI treatments combined with other forms of cancer therapy including ablative options. Clinical work by Zhu et al showed a significant reduction of metastatic lesions in patients with cervical carcinosarcoma when treated with a PD-1 blocker, pembrolizumab, following cryoablation 119 . No lesions were detected on CT images at 1.5 months post administration of pembrolizumab, and it was remained for 7 months after the treatment.…”
Section: Combination Cryoablation Cancer Therapiesmentioning
confidence: 99%